2017
DOI: 10.2754/avb201786010003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Staphylococcus aureus in cattle, sheep, goat, and pig rearing in the Czech Republic

Abstract: The study focused on the prevalence of Staphylococcus aureus and resistant strains in livestock. In this study, 114 different samples from three cattle farms (84 from two farms of dairy cows and 30 from one farm of suckler cows), 132 samples from one sheep farm, 120 samples from one goat farm, and 82 samples from three pig farms were examined. Strains identified as Staphylococcus aureus were further analysed by the polymerase chain reaction method for detection of the mecA gene and for confirmation of the sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
8
1
1
Order By: Relevance
“…We found high levels of resistance to gentamycin and ciprofloxacin in milk and human isolates (Table -9), which agreed with the findings of Hoque et al, Zeinhom et al,Ameen et al,Reta et al and Klimešová et al [30,35,61,62]. These authors also detected high resistance to gentamycin in animal [63] in Egypt found increased resistance in S. aureus isolates from clinical mastitis to penicillin and gentamicin.…”
Section: Resultssupporting
confidence: 91%
“…We found high levels of resistance to gentamycin and ciprofloxacin in milk and human isolates (Table -9), which agreed with the findings of Hoque et al, Zeinhom et al,Ameen et al,Reta et al and Klimešová et al [30,35,61,62]. These authors also detected high resistance to gentamycin in animal [63] in Egypt found increased resistance in S. aureus isolates from clinical mastitis to penicillin and gentamicin.…”
Section: Resultssupporting
confidence: 91%
“…The resistance (40.63%) of the isolates to tetracycline in this study may reflect the excessive use of the drug in treatment in the study area. The susceptibility by S. aureus isolates to chloramphenicol, gentamicin and kanamycin observed in this study is comparable with the findings of Klimesova et al (2017) who reported resistance to chloramphenicol to be 15.63 %. The high proportion of susceptibility by the isolates to nitrofurantoin (84.38%), ciprofloxacin (78.13%) and chloramphenicol (78.13%) is suggestive of the potential efficacy of these drugs in treating MRSA infections and may reflect the fact that they may be less commonly abused in the environment.…”
Section: Resultssupporting
confidence: 90%
“…This behavior can be performed on self-grooming or on another animal (allogrooming) and, due to this behavior, it is possible that the animals in this work have crossed contamination, justifying the high resistance index of these samples. [38][39][40] The origin of to antimicrobials is not completely defined and may have different genetic origins, for example, the genes encoding blaZ resistance 31,32 which, like mecA, 33 are responsible for resistance to penicillins. Therefore, in this work, the presence of the mecA gene in oxacillin-resistant isolates was investigated and no positive sample was detected.…”
Section: Discussionmentioning
confidence: 99%